(untitled) (Revista de Ciências Agroveterinárias, 2015)
The objective of this study was to evaluate the nutritional value of ryegrass (Lolium multiflorum Lam) cv. Barjumbo and common ryegrass (Lolium multiflorum) intercropped or not with oats (Avena strigosa Schreb) cv. IAPAR 61 under two post-grazing residue. The study was conducted at the Universidade Tecnológica Federal do Paraná, Câmpus Dois Vizinhos, in the period April-September, 2012. The experimental design was a bifactorial 4x2, totaling eight treatments with three replicates, common and Barjumbo ryegrass single or intercropped with oat in two post-grazing residue: High: 50% of the input height; Low: 30% of the input height being evaluated. The variables evaluated were crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), total digestible nutrients (TDN) and in vitro dry matter digestibility (IVDMD). The single Barjumbo had higher CP. NDF and ADF were lower for single cultivar or intercropped Barjumbo in comparison to the common cultivar and, consequently, the IVDMD and TDN were higher. Within the trial period, the grazing slightly increased the CP content, TDN and IVDMD until about 100 days after emergence. The NDF and ADF values have showed a linear increase from the beginning to the end of the trial period.